Efektivitas Perintah Pencatatan Perceraian dalam Putusan Verstek: Studi Kasus Pengadilan Negeri Airmadidi Nomor 224/Pdt.G/2024/PN Arm - Reynold Simandjuntak; Loisa Windy Lapondu; Jeremy D. Rumimpunu; Sari Clarisya Sihombing; Meren Priskila Majid; Susan Tiur Mida Sianturi; Jesica Kumolontang; Moristi R.N. Runtunuwu (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the effectiveness of divorce registration orders in court decisions, particularly in default verdict cases, and to identify obstacles and solutions within Indonesia’s civil registration system. The analysis reveals that although divorce registration orders are normatively regulated under Law Number 1 of 1974 on Marriage and Ministry of Home Affairs Regulation Number 108 of 2019, their implementation still faces various challenges such as lack of inter-agency information system integration, limited human resources and infrastructure, and low public awareness. This ineffectiveness potentially causes legal uncertainty and administrative problems for citizens. Therefore, this study recommends strengthening digital system integration, enhancing human resource capacity, conducting extensive legal socialization, improving service infrastructure, reinforcing data security, and enforcing strict supervision and law enforcement. The implementation of these recommendations is expected to improve the effectiveness of divorce registration and strengthen the protection of civil rights for Indonesian citizens.